Para além da narrativa de sucesso: uma análise pós-colonial e interseccional da Agenda Mulheres, Paz e Segurança na MINUSCA - Cortelini, Eduarda Racoski (2022)
This dissertation proposes to perform an intersectional and postcolonial analysis of the Women, Peace, and Security Agenda (WPS) in MINUSCA (United Nations Multidimensional Integrated Stabilization Mission In The Central African Republic) from 2014 to 2021. Divided into four investigation topics, this dissertation analyzed: a) women's participation in peacekeeping operations; b) the pre-deployment capacitation of the women and the training in gender issues; c) the prevention of gender violence and the performance of Gender Advisers in MINUSCA and d) the dynamics of race that reflect the racism and xenophobia in the institutional and interpersonal environment. Utilizing the Case Study methodology, the main sources of this analysis were MINUSCA's quarterly reports from 2014-2021 and the interviews done with Brazilian women that participated in the operation. In theoretical terms, this study uses the contributions of Scott (1990) about the gender concept, looking for analyzing how the State has patriarchal bases (PATEMAN, 1993) and, from that, how a feminist approach is necessary for the studies of International Security to analyze international institutions and practices (PETERSON, 1992; TICKNER, 1992, 2001;SJOBERG, 2009). Similarly, Connell’s concept of Hegemonic Masculinity (1995) helps us to understand how militarized institutions have a gendered culture (CARREIRAS,2010) and how it affects the military practices, state policies, and security discourses. In the end, this work sought to map the origins, intentions, and colonial language of the WPS Agenda (PARASHAR,2018) from the postcolonial (HALL, 2003) e intersectional perspective (CRENSHAW, 1991, 2002; HILL COLLINS, BILGE, 2021). In conclusion, MINUSCA's quarterly reports, as well as other data provided by the United Nations, although comprehensive, are insufficient to understand all the dynamics that occur on the ground. Only the micro and macro analyzes, structural and subjective, with an intersectional approach, is capable of comprehending the power dynamics present in these locals and proposing strategies that consider the local context in which the MPS Agenda operates.